SAT0127 Child Outcome after Certolizumab Pegol Exposure in Rheumatoid Arthritis Pregnancies: A Case Series Report. (15th July 2016) - Meroni, M.; Ramoni, V.L.; Brucato, A.L.; Limonta, M.; Ostensen, M.; Cutolo, M.
Abstract : Background: About 25% of pregnant RA patients remain active during pregnancy and need continuation of effective therapy to maintain low disease activity [1]. Recent evidence supports the use of TNF inhibitors (TNFi) to achieve these goals [2]. The overall safety of TNFi exposure during pregnancy has been demonstrated [3–4]. Certolizumab pegol (CZP) has received particular interest because of its low transplacental transfer, an advantage compared to several other TNFi [5]. A recent study analyzing CZP exposure during gestation has not shown harmful effects on pregnancy outcomes [6]. Since there are few data on child outcome, our case series adds observations on the safety of CZP in pregnancy. Objectives: The study purpose consists in assessing CZP exposure safety during pregnancy in a group of RA patients. Methods: During a 48 months period, we retrospectively evaluated 8 RA patients exposed to CZP in the 1st and/or the 2nd trimester of pregnancy. All patients had signed an informed consent regarding the potential risk of biologic agents for the fetus. Details regarding demographic and clinical presentation as well as pregnancy outcome and child health were collected. Data on child development during the first 6 months of life were obtained. Results: The eight enrolled patients had been treated with CZP for 6 to 18 months. Three patients received methotrexate (MTX) and other TNFi (infliximab or etanercept) before pregnancy, which were discontinued 6–24 months before conception. During pregnancy all patients were treated with the standard dose of CZP 200 mg every 2 or 3 weeks. In addition, all patients received low-dose prednisone ranging from 5±2.5 mg daily. Two subjects were in addition on sulfasalazine 500 mg x 3/day, and three others on hydroxychloroquine (HCQ) 200 mg twice daily. In 6/8 patients, CZP treatment was continued throughout the first trimester. In 2 cases high disease activity required continuation of CZP until the end of the second trimester. No obstetric, neonatal or perinatal severe complication was observed. Except for one SGA child all neonates were healthy at birth. One child was hospitalized at the age of 4 months for disseminated Candida albicans infection, but recovered completely with amphotericin B treatment. All other children developed normally during the first 6 months of life. None of the newborn was breastfed, due to the lack of data on safety. All babies were vaccinated according to the mandatory Italian schedule (includes no live vaccine during the first 6 months of life); one child had the 5th month dose postponed to the 6th month of life. Conclusions: The limits of our case series consist in the small numbers and the lack of measuring CZP levels in cord blood. However, our data add to the experience that CZP might be considered in pregnant RA patients when disease activity requires continuation of therapy throughout pregnancy. References: Østensen M, et al. Autoimm Rev 2015;14:370–86. Chambers CD, et al. Birth Defects Res A Clin Mol Teratol 2012;94:607–11. Marchioni RM, et al. World J Gastroenterol 2013;19:2591–602. Weber-Schoendorfer C, et al. Br J Clin Pharmacol. 2015;80:727–39. Mahadevan U, et al. Clin Gastroenterol Hepatol 2013;11:293–4. Clowse MED, et al. J Rheumatol 2015;42:2270–8. Disclosure of Interest: None declared